Titanium coating with hydroxyapatite and chitosan doped with silver nitrate - De Sousa, Lucíola Lucena (2017)
Biomaterials are effective alternatives for tissue substitution, including the bone tissue, since they do not pose risks of transmission of diseases or immune rejection. Nowadays, there is an interest in new materials capable of being associated with other substances which favor bone formation, especially natural biopolymers, in particular chitosan, which may present a potential for repairing bone defects and forms films that adhere to metal surfaces. Titanium, despite being a material greatly employed in implants because of its excellent physical properties, does not present bioactive characteristics, making it necessary to use methods of surface modification to enhance its biological response, favoring bone formation. This work aims at studying commercially pure titanium (cp-Ti) coating with chitosan using the biomimetic method and the evaluation of the effects of process variables as substrate surface conditions. Subsequently, the incorporation of AgNO3 was studied and its effects on corrosion resistance were evaluated. To evaluate the coating process, several tests were conducted, such as scanning electron microscopy, X-ray diffraction and infrared spectroscopy. From the results obtained, the efficacy of the chitosan film in inhibiting the corrosion of the metals is concluded, which was the target of this study, thus justifying its use for osseointegration and in several implants.